A nano silver ion conductive coating material and preparation method thereof
By preparing nano-silver ion conductive coating materials and using raw materials such as modified resin, modified fillers and nano-silver, the problem of poor conductivity of existing conductive coating materials has been solved, and high conductivity and good coating film hardness have been achieved. Enhanced its application potential in multiple industrial fields.
Patent Information
- Application Number
- CN202410598385.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-05-15
AI Technical Summary
At this stage, the conductive coating material has poor conductivity, which limits its application in various industrial fields.
Using the preparation method of nano-silver ion conductive coating material, the conductive coating material is prepared by uniformly mixing raw materials such as modified resin, modified filler, nano-silver, photoinitiator and zinc sulfate hexahydrate solution. The method involves a multi-step reaction and treatment process to ensure the material's efficient conductivity and stability.
It achieves high conductivity and good coating film hardness of conductive coating materials, improving its application potential in aviation, electronic appliances, construction and other fields.
Smart Images

Figure BDA0004839682290000111
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of conductive coating preparation, and in particular to a nano silver ion conductive coating material and a preparation method thereof. Background Art
[0002] Conductive coating is a special functional coating that can provide the system with conductivity by coating on the surface of non-conductive objects. With the continuous improvement of modern science and technology, the functional coating that can give high molecular polymers the ability to conduct static electricity has been rapidly developed and has been widely used in many industrial fields such as aviation, electronics, construction, chemicals, printing, etc. Conductive coating has the conductivity of metal materials and the excellent mechanical properties of polymer materials, and the construction process is simple, which is convenient for surface coating of various objects, making it widely concerned in the field of electromagnetic repair. At present, the conductivity of conductive coatings is average, which hinders the use of conductive coatings. Summary of the invention
[0003] The purpose of the present invention is to provide a method for preparing a nano silver ion conductive coating material to solve the problem that the conductive effect of the coating material is poor at present.
[0004] The purpose of the present invention can be achieved through the following technical solutions:
[0005] A method for preparing a nano silver ion conductive coating material comprises the following steps:
[0006] Step A1: Mix benzo[1,2-B:4,5-B']dithiophene-4,8-dione, p-bromophenol and tetrahydrofuran evenly, stir and add n-butyl lithium at a speed of 120-150 r / min and a temperature of minus 78° C., stir for 3-5 hours, heat to 20-25° C., continue to react for 10-12 hours, add tin chloride dihydrate and hydrochloric acid solution, and continue to react for 3-5 hours to obtain a modified monomer;
[0007] Step A2: uniformly mix polycarbonate diol, 2,2-bis(hydroxymethyl)propionic acid, modified monomer and tetrahydrofuran, stir and add isophorone diisocyanate and dibutyltin dilaurate at a speed of 60-80 r / min and a temperature of 50-60° C., react for 3-5 hours, add triethylamine, react for 30-40 minutes, add hydroxyethyl methacrylate, continue to react for 6-8 hours, distill off tetrahydrofuran to obtain a modified resin, and disperse the modified resin in deionized water to obtain a modified resin emulsion;
[0008] Step A3: Weigh the following raw materials in parts by weight: 80-100 parts of modified resin emulsion, 15-20 parts of modified filler, 5-10 parts of nanosilver, 3-5 parts of photoinitiator and 30-50 parts of zinc sulfate hexahydrate solution, mix the raw materials evenly, and prepare a conductive coating material.
[0009] Furthermore, the dosage ratio of benzo[1,2-B:4,5-B']dithiophene-4,8-dione, p-bromophenol, n-butyllithium, tin chloride dihydrate and hydrochloric acid solution in step A1 is 10 mmol:20 mmol:29 mmol:100 mmol:20 mL, and the mass number of the hydrochloric acid solution is 15%.
[0010] Furthermore, the molar ratio of the polycarbonate diol, 2,2-bis(hydroxymethyl)propionic acid, modified monomer, isophorone diisocyanate, triethylamine and hydroxyethyl methacrylate described in step A2 is 3:1:2:7:1:2.2, the molecular weight of the polycarbonate diol is 2000, and the amount ratio of the modified resin and deionized water is 1g:4mL.
[0011] Furthermore, the photoinitiator described in step A3 is one of photoinitiator 819, photoinitiator 1173 and photoinitiator 2959, and the mass fraction of zinc sulfate hexahydrate solution is 15%.
[0012] Further, the modified filler is prepared by the following steps:
[0013] Step B1: dispersing graphene in ethanol, stirring and adding deionized water and KH550 at a speed of 150-200 r / min and a temperature of 40-50° C., reacting for 3-5 hours to obtain pretreated graphene, and uniformly mixing 2-formyl-1,4-benzenedicarboxylic acid, copper acetate, DMF and deionized water, reacting for 10-15 hours at a speed of 60-80 r / min and a temperature of 40-50° C. to obtain a copper organic framework;
[0014] Step B2: pretreated graphene, copper organic framework and DMF are mixed, stirred and hydrogen peroxide is added to pH value of 6-6.5 at a speed of 120-150r / min and a temperature of 40-50°C, and the reaction is carried out for 8-10h to obtain modified graphene, and the modified graphene, 4-nitro-o-phenylenediamine, potassium carbonate and anhydrous ethanol are mixed uniformly, and refluxed for 10-15h at a speed of 150-200r / min and a temperature of 78-80°C, and the pH value is adjusted to 5-5.5 to obtain a precursor;
[0015] Step B3: Mix zinc powder, ammonium chloride and deionized water, stir for 1-1.5 hours at a speed of 120-150r / min and a temperature of 80-85°C, add a precursor, react for 6-8 hours, add sodium hydroxide until the pH is alkaline to obtain a modified precursor, mix the modified precursor, acrylic acid, dicyclohexylcarbodiimide and DMF, react for 3-5 hours at a speed of 120-150r / min and a temperature of 30-40°C, filter to remove the filtrate and dry to obtain a modified filler.
[0016] Furthermore, the amount of KH550 used in step B1 is 1% by mass of graphene, and the molar ratio of 2-formyl-1,4-benzenedicarboxylic acid to copper acetate is 2:1.
[0017] Furthermore, the molar ratio of the amino groups on the pretreated graphene and the aldehyde groups on the copper organic framework in step B2 is 1:2, and the molar ratio of the aldehyde groups on the precursor, 4-nitro-o-phenylenediamine and potassium carbonate is 1:1.1:1.5.
[0018] Furthermore, the mass ratio of the zinc powder, ammonium chloride and the precursor in step B3 is 2.3:1:2, and the molar ratio of the amino group, acrylic acid and dicyclohexylcarbodiimide on the modified precursor is 1:1:1.2.
[0019] Beneficial effects of the invention: A nano silver ion conductive coating material disclosed in the invention comprises the following raw materials: a modified resin emulsion, a modified filler, nano silver, a photoinitiator and a zinc sulfate hexahydrate solution, wherein the modified resin liquid reacts with benzo[1,2-B:4,5-B']dithiophene-4,8-dione and p-bromophenol as raw materials, so that the ketone group on benzo[1,2-B:4,5-B']dithiophene-4,8-dione reacts with the bromine atom site on p-bromophenol to obtain a modified monomer, and polycarbonate diol, 2,2-bis( The prepolymer is formed by reacting hydroxymethyl) propionic acid, a modified monomer and isophorone diisocyanate, which are neutralized with triethylamine, capped with hydroxyethyl methacrylate, and finally blended with deionized water to obtain a modified resin emulsion. The modified filler is treated with KH550 using graphene as a raw material, so that active amino groups are grafted on the surface to obtain pretreated graphene. 2-formyl-1,4-benzenedicarboxylic acid and copper acetate are complexed to obtain a copper organic framework. The pretreated graphene is reacted with the copper organic framework so that the amino groups on the pretreated graphene react with the aldehyde groups on the copper organic framework. The structure of the copper organic framework coated pre-treated graphene is formed to obtain modified graphene, the modified graphene is reacted with 4-nitro-o-phenylenediamine, so that the aldehyde group on the precursor reacts with the diamino group on the 4-nitro-o-phenylenediamine to form an imidazole group to obtain a precursor, the precursor is reduced with zinc powder and ammonium chloride to convert the nitro group on the precursor into an amino group to obtain a modified precursor, the amino group on the modified precursor is reacted with acrylic acid for dehydration reaction to graft double bonds on the surface, and the coating film is irradiated with ultraviolet rays during the coating process and crosslinked under the action of a photoinitiator. Cross-linking curing, the surface of the modified filler contains double bonds, which can cross-link with the modified resin molecules. The modified filler contains imidazole groups. When the coating is cured, the imidazole groups can cooperate with the zinc ions in the zinc sulfate hexahydrate solution, thereby increasing the electron transfer at the cross-linking point. At the same time, the modified resin contains a thiophene ring structure, and thiophene contains a π bridge structure, which can absorb electrons. Nanosilver has a high conductivity, and its oxidation product is still conductive. When the modified resin, modified filler and nanosilver are combined, a stable charge transport network can be formed, thereby forming a conductive grid. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Example 1
[0022] A method for preparing a nano silver ion conductive coating material comprises the following steps:
[0023] Step A1: Benzo[1,2-B:4,5-B']dithiophene-4,8-dione, p-bromophenol and tetrahydrofuran are uniformly mixed, stirred at a speed of 120 r / min and a temperature of minus 78°C, and n-butyl lithium is added. After stirring for 3 hours, the temperature is raised to 20°C, and the reaction is continued for 10 hours. Tin chloride dihydrate and hydrochloric acid solution are added, and the reaction is continued for 3 hours to obtain a modified monomer;
[0024] Step A2: polycarbonate diol, 2,2-bis(hydroxymethyl)propionic acid, modified monomer and tetrahydrofuran are uniformly mixed, and isophorone diisocyanate and dibutyltin dilaurate are added under stirring at a speed of 60 r / min and a temperature of 50° C. to react for 3 h, triethylamine is added, and the reaction is carried out for 30 min, hydroxyethyl methacrylate is added, and the reaction is continued for 6 h, tetrahydrofuran is distilled off to obtain a modified resin, and the modified resin is dispersed in deionized water to obtain a modified resin emulsion;
[0025] Step A3: Weigh the following raw materials in parts by weight: 80 parts of modified resin emulsion, 15 parts of modified filler, 5 parts of nanosilver, 3 parts of photoinitiator and 30 parts of zinc sulfate hexahydrate solution, mix the raw materials evenly, and prepare a conductive coating material.
[0026] The amount ratio of benzo[1,2-B:4,5-B']dithiophene-4,8-dione, p-bromophenol, n-butyllithium, tin chloride dihydrate and hydrochloric acid solution described in step A1 is 10 mmol:20 mmol:29 mmol:100 mmol:20 mL, and the mass number of the hydrochloric acid solution is 15%.
[0027] The molar ratio of the polycarbonate diol, 2,2-bis(hydroxymethyl)propionic acid, modified monomer, isophorone diisocyanate, triethylamine and hydroxyethyl methacrylate described in step A2 is 3:1:2:7:1:2.2, the molecular weight of the polycarbonate diol is 2000, and the amount ratio of the modified resin and deionized water is 1g:4mL.
[0028] The photoinitiator described in step A3 is photoinitiator 819, and the mass fraction of zinc sulfate hexahydrate solution is 15%.
[0029] The modified filler is prepared by the following steps:
[0030] Step B1: dispersing graphene in ethanol, stirring and adding deionized water and KH550 at a speed of 150 r / min and a temperature of 40° C., reacting for 3 h to obtain pretreated graphene, and mixing 2-formyl-1,4-benzenedicarboxylic acid, copper acetate, DMF and deionized water evenly, reacting for 10 h at a speed of 60 r / min and a temperature of 40° C. to obtain a copper organic framework;
[0031] Step B2: pretreated graphene, copper organic framework and DMF were mixed, stirred and hydrogen peroxide was added to pH 6 at a speed of 120 r / min and a temperature of 40°C, and the reaction was carried out for 8 hours to obtain modified graphene; modified graphene, 4-nitro-o-phenylenediamine, potassium carbonate and anhydrous ethanol were mixed evenly, refluxed for 10 hours at a speed of 150 r / min and a temperature of 78°C, and the pH value was adjusted to 5 to obtain a precursor;
[0032] Step B3: Mix zinc powder, ammonium chloride and deionized water, stir for 1 hour at a speed of 120 r / min and a temperature of 80°C, add a precursor, react for 6 hours, add sodium hydroxide until the pH is alkaline to obtain a modified precursor, mix the modified precursor, acrylic acid, dicyclohexylcarbodiimide and DMF, react for 3 hours at a speed of 120 r / min and a temperature of 30°C, filter to remove the filtrate and dry to obtain a modified filler.
[0033] The amount of KH550 used in step B1 is 1% by mass of graphene, and the molar ratio of 2-formyl-1,4-benzenedicarboxylic acid to copper acetate is 2:1.
[0034] The molar ratio of the amino groups on the pretreated graphene and the aldehyde groups on the copper organic framework described in step B2 is 1:2, and the molar ratio of the aldehyde groups on the precursor, 4-nitro-o-phenylenediamine and potassium carbonate is 1:1.1:1.5.
[0035] The mass ratio of the zinc powder, ammonium chloride and the precursor in step B3 is 2.3:1:2, and the molar ratio of the amino group, acrylic acid and dicyclohexylcarbodiimide on the modified precursor is 1:1:1.2.
[0036] Example 2
[0037] A method for preparing a nano silver ion conductive coating material comprises the following steps:
[0038] Step A1: Benzo[1,2-B:4,5-B']dithiophene-4,8-dione, p-bromophenol and tetrahydrofuran are uniformly mixed, stirred at a speed of 120 r / min and a temperature of minus 78° C., and n-butyl lithium is added. After stirring for 4 hours, the temperature is raised to 23° C., and the reaction is continued for 11 hours. Tin chloride dihydrate and hydrochloric acid solution are added, and the reaction is continued for hours to obtain a modified monomer;
[0039] Step A2: polycarbonate diol, 2,2-bis(hydroxymethyl)propionic acid, modified monomer and tetrahydrofuran are uniformly mixed, and isophorone diisocyanate and dibutyltin dilaurate are added under stirring at a speed of 60 r / min and a temperature of 55° C. to react for 4 hours, triethylamine is added, and the reaction is carried out for 35 minutes, hydroxyethyl methacrylate is added, and the reaction is continued for 7 hours, and tetrahydrofuran is distilled off to obtain a modified resin, and the modified resin is dispersed in deionized water to obtain a modified resin emulsion;
[0040] Step A3: Weigh the following raw materials in parts by weight: 90 parts of modified resin emulsion, 18 parts of modified filler, 8 parts of nanosilver, 4 parts of photoinitiator and 40 parts of zinc sulfate hexahydrate solution, mix the raw materials evenly, and prepare a conductive coating material.
[0041] The amount ratio of benzo[1,2-B:4,5-B']dithiophene-4,8-dione, p-bromophenol, n-butyllithium, tin chloride dihydrate and hydrochloric acid solution described in step A1 is 10 mmol:20 mmol:29 mmol:100 mmol:20 mL, and the mass number of the hydrochloric acid solution is 15%.
[0042] The molar ratio of the polycarbonate diol, 2,2-bis(hydroxymethyl)propionic acid, modified monomer, isophorone diisocyanate, triethylamine and hydroxyethyl methacrylate described in step A2 is 3:1:2:7:1:2.2, the molecular weight of the polycarbonate diol is 2000, and the amount ratio of the modified resin and deionized water is 1g:4mL.
[0043] The photoinitiator described in step A3 is photoinitiator 1173, and the mass fraction of zinc sulfate hexahydrate solution is 15%.
[0044] The modified filler is prepared by the following steps:
[0045] Step B1: dispersing graphene in ethanol, stirring and adding deionized water and KH550 at a speed of 150 r / min and a temperature of 45° C., reacting for 4 hours to obtain pretreated graphene, and mixing 2-formyl-1,4-benzenedicarboxylic acid, copper acetate, DMF and deionized water evenly, reacting for 13 hours at a speed of 60 r / min and a temperature of 45° C. to obtain a copper organic framework;
[0046] Step B2: pretreated graphene, copper organic framework and DMF were mixed, stirred and hydrogen peroxide was added to pH 6.5 at a speed of 120 r / min and a temperature of 45°C, and the reaction was carried out for 9 hours to obtain modified graphene; modified graphene, 4-nitro-o-phenylenediamine, potassium carbonate and anhydrous ethanol were mixed uniformly, refluxed at a speed of 150 r / min and a temperature of 80°C for 13 hours, and the pH value was adjusted to 5.5 to obtain a precursor;
[0047] Step B3: Mix zinc powder, ammonium chloride and deionized water, stir for 1.5 hours at a speed of 120 r / min and a temperature of 83°C, add a precursor, react for 7 hours, add sodium hydroxide until the pH is alkaline to obtain a modified precursor, mix the modified precursor, acrylic acid, dicyclohexylcarbodiimide and DMF, react for 4 hours at a speed of 120 r / min and a temperature of 35°C, filter to remove the filtrate and dry to obtain a modified filler.
[0048] The amount of KH550 used in step B1 is 1% by mass of graphene, and the molar ratio of 2-formyl-1,4-benzenedicarboxylic acid to copper acetate is 2:1.
[0049] The molar ratio of the amino groups on the pretreated graphene and the aldehyde groups on the copper organic framework described in step B2 is 1:2, and the molar ratio of the aldehyde groups on the precursor, 4-nitro-o-phenylenediamine and potassium carbonate is 1:1.1:1.5.
[0050] The mass ratio of the zinc powder, ammonium chloride and the precursor in step B3 is 2.3:1:2, and the molar ratio of the amino group, acrylic acid and dicyclohexylcarbodiimide on the modified precursor is 1:1:1.2.
[0051] Example 3
[0052] A method for preparing a nano silver ion conductive coating material comprises the following steps:
[0053] Step A1: Benzo[1,2-B:4,5-B']dithiophene-4,8-dione, p-bromophenol and tetrahydrofuran are uniformly mixed, stirred at a speed of 150 r / min and a temperature of minus 78° C., and n-butyl lithium is added. After stirring for 5 hours, the temperature is raised to 25° C., and the reaction is continued for 12 hours. Tin chloride dihydrate and hydrochloric acid solution are added, and the reaction is continued for 5 hours to obtain a modified monomer;
[0054] Step A2: polycarbonate diol, 2,2-bis(hydroxymethyl)propionic acid, modified monomer and tetrahydrofuran are uniformly mixed, and isophorone diisocyanate and dibutyltin dilaurate are added under stirring at a speed of 80 r / min and a temperature of 60° C. to react for 5 h, triethylamine is added, and the reaction is carried out for 40 min, hydroxyethyl methacrylate is added, and the reaction is continued for 8 h, tetrahydrofuran is distilled off to obtain a modified resin, and the modified resin is dispersed in deionized water to obtain a modified resin emulsion;
[0055] Step A3: Weigh the following raw materials in parts by weight: 100 parts of modified resin emulsion, 20 parts of modified filler, 10 parts of nanosilver, 5 parts of photoinitiator and 50 parts of zinc sulfate hexahydrate solution, mix the raw materials evenly, and prepare a conductive coating material.
[0056] The amount ratio of benzo[1,2-B:4,5-B']dithiophene-4,8-dione, p-bromophenol, n-butyllithium, tin chloride dihydrate and hydrochloric acid solution described in step A1 is 10 mmol:20 mmol:29 mmol:100 mmol:20 mL, and the mass number of the hydrochloric acid solution is 15%.
[0057] The molar ratio of the polycarbonate diol, 2,2-bis(hydroxymethyl)propionic acid, modified monomer, isophorone diisocyanate, triethylamine and hydroxyethyl methacrylate described in step A2 is 3:1:2:7:1:2.2, the molecular weight of the polycarbonate diol is 2000, and the amount ratio of the modified resin and deionized water is 1g:4mL.
[0058] The photoinitiator described in step A3 is photoinitiator 2959, and the mass fraction of zinc sulfate hexahydrate solution is 15%.
[0059] The modified filler is prepared by the following steps:
[0060] Step B1: dispersing graphene in ethanol, stirring and adding deionized water and KH550 at a speed of 200 r / min and a temperature of 50° C., reacting for 5 hours to obtain pretreated graphene, and mixing 2-formyl-1,4-benzenedicarboxylic acid, copper acetate, DMF and deionized water evenly, reacting for 15 hours at a speed of 80 r / min and a temperature of 50° C. to obtain a copper organic framework;
[0061] Step B2: pretreated graphene, copper organic framework and DMF were mixed, stirred and hydrogen peroxide was added to pH 6.5 at a speed of 150 r / min and a temperature of 50°C, and the reaction was carried out for 10 hours to obtain modified graphene; modified graphene, 4-nitro-o-phenylenediamine, potassium carbonate and anhydrous ethanol were mixed uniformly, refluxed at a speed of 200 r / min and a temperature of 80°C for 15 hours, and the pH value was adjusted to 5.5 to obtain a precursor;
[0062] Step B3: Mix zinc powder, ammonium chloride and deionized water, stir for 1.5 hours at a speed of 150 r / min and a temperature of 85°C, add a precursor, react for 8 hours, add sodium hydroxide until the pH is alkaline to obtain a modified precursor, mix the modified precursor, acrylic acid, dicyclohexylcarbodiimide and DMF, react for 5 hours at a speed of 150 r / min and a temperature of 40°C, filter to remove the filtrate and dry to obtain a modified filler.
[0063] The amount of KH550 used in step B1 is 1% by mass of graphene, and the molar ratio of 2-formyl-1,4-benzenedicarboxylic acid to copper acetate is 2:1.
[0064] The molar ratio of the amino groups on the pretreated graphene and the aldehyde groups on the copper organic framework described in step B2 is 1:2, and the molar ratio of the aldehyde groups on the precursor, 4-nitro-o-phenylenediamine and potassium carbonate is 1:1.1:1.5.
[0065] The mass ratio of the zinc powder, ammonium chloride and the precursor in step B3 is 2.3:1:2, and the molar ratio of the amino group, acrylic acid and dicyclohexylcarbodiimide on the modified precursor is 1:1:1.2.
[0066] Comparative Example 1
[0067] Compared with Example 1, no modified monomer was added in this comparative example, and the remaining steps were the same.
[0068] Comparative Example 2
[0069] Compared with Example 1, this comparative example uses graphene instead of the modified filler, and the remaining steps are the same.
[0070] Comparative Example 3
[0071] Compared with Example 1, this comparative example uses copper organic framework instead of modified graphene, and the other steps are the same.
[0072] Comparative Example 4
[0073] Compared with Example 1, benzaldehyde, 4-nitro-o-phenylenediamine, potassium carbonate and anhydrous ethanol were uniformly mixed, and refluxed for 10 hours at a speed of 150 r / min and a temperature of 78° C., and the pH value was adjusted to 5. The obtained product replaced the precursor, and the remaining steps were the same.
[0074] The conductive coatings prepared in Examples 1-3 and Comparative Examples 1-4 were sprayed on release paper with a film thickness of 25 μm. After curing and peeling, the paper was cut into a pattern with a size of 30 mm×30 mm. The resistance of the prepared coatings was tested in accordance with the standard of GB / T16906-1997 using a KEYSIGHT B2985A electrometer / high resistance meter, 3M conductive glue and silver glue dot platinum wire. The test voltage was 100 V, and the surface resistivity was tested. In accordance with the standard of GB / T6739-2006, the hardness of the coating was tested. The test results are shown in the following table.
[0075]
[0076] From the above table, we can see that the application has good conductivity and coating hardness.
[0077] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a nano silver ion conductive coating material, characterized in that: The specific steps include: Step A1: benzo[1,2-B:4,5-B']dithiophene-4,8-dione, p-bromophenol and tetrahydrofuran are mixed and stirred, and n-butyl lithium is added. After stirring, the temperature is raised to react, and then tin chloride dihydrate and hydrochloric acid solution are added to continue the reaction to obtain a modified monomer; Step A2: polycarbonate diol, 2,2-bis(hydroxymethyl)propionic acid, a modified monomer and tetrahydrofuran are mixed and stirred, and isophorone diisocyanate and dibutyltin dilaurate are added to react, triethylamine is added to react, hydroxyethyl methacrylate is added to continue the reaction, tetrahydrofuran is distilled off to obtain a modified resin, and the modified resin is dispersed in deionized water to obtain a modified resin emulsion; Step A3: Weigh the following raw materials in parts by weight: 80-100 parts of modified resin emulsion, 15-20 parts of modified filler, 5-10 parts of nanosilver, 3-5 parts of photoinitiator and 30-50 parts of zinc sulfate hexahydrate solution, mix the raw materials evenly, and prepare a conductive coating material; The modified filler is prepared by the following steps: Step B1: dispersing graphene in ethanol, stirring and adding deionized water and KH550 to react to obtain pretreated graphene, and mixing 2-formyl-1,4-benzenedicarboxylic acid, copper acetate, DMF and deionized water to react to obtain a copper organic framework; Step B2: pretreated graphene, copper organic framework and DMF are mixed and stirred and hydrogen peroxide is added to react to obtain modified graphene; modified graphene, 4-nitro-o-phenylenediamine, potassium carbonate and anhydrous ethanol are mixed and refluxed to react, and pH is adjusted to be acidic to obtain a precursor; Step B3: Mix zinc powder, ammonium chloride and deionized water, add the precursor, react for 6-8 hours, add sodium hydroxide until the pH is alkaline to obtain a modified precursor, mix the modified precursor, acrylic acid, dicyclohexylcarbodiimide and DMF to react, filter to remove the filtrate and dry to obtain a modified filler.
2. The method for preparing a nano silver ion conductive coating material according to claim 1, characterized in that: The amount ratio of benzo[1,2-B:4,5-B']dithiophene-4,8-dione, p-bromophenol, n-butyllithium, tin chloride dihydrate and hydrochloric acid solution in step A1 is 10 mmol:20 mmol:29 mmol:100 mmol:20 mL.
3. The method for preparing a nano silver ion conductive coating material according to claim 1, characterized in that: The molar ratio of the polycarbonate diol, 2,2-bis(hydroxymethyl)propionic acid, modified monomer, isophorone diisocyanate, triethylamine and hydroxyethyl methacrylate described in step A2 is 3:1:2:7:1:2.2, and the amount ratio of the modified resin and deionized water is 1g:4mL.
4. The method for preparing a nano silver ion conductive coating material according to claim 1, characterized in that: The photoinitiator described in step A3 is one of photoinitiator 819, photoinitiator 1173 and photoinitiator 2959.
5. The method for preparing a nano silver ion conductive coating material according to claim 1, characterized in that: The amount of KH550 used in step B1 is 1% by mass of graphene, and the molar ratio of 2-formyl-1,4-benzenedicarboxylic acid to copper acetate is 2:
1.
6. The method for preparing a nano silver ion conductive coating material according to claim 1, characterized in that: The molar ratio of the amino groups on the pretreated graphene and the aldehyde groups on the copper organic framework described in step B2 is 1:2, and the molar ratio of the aldehyde groups on the precursor, 4-nitro-o-phenylenediamine and potassium carbonate is 1:1.1:1.
5.
7. The method for preparing a nano silver ion conductive coating material according to claim 1, characterized in that: The mass ratio of the zinc powder, ammonium chloride and the precursor in step B3 is 2.3:1:2, and the molar ratio of the amino group, acrylic acid and dicyclohexylcarbodiimide on the modified precursor is 1:1:1.2.
Citation Information
Patent Citations
2,6-bis(triphenylamine)-4,8-bis(alkoxy)benzo[1,2-b:4,5-b']bithiophene and preparation for same
CN105968124A
Foam graphene-based metal azide compound and preparation method thereof
CN111422855A